Abu Dhabi International Petroleum Exhibition and Conference 2002
DOI: 10.2118/78534-ms
|View full text |Cite
|
Sign up to set email alerts
|

Karstic high permeability layers: Characterization and Preservation while modeling carbonate reservoirs

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractDiagnosis, characterization and modeling of high permeability layers constitute a very challenging issue while building carbonate reservoir models for flow simulation.In karstic reservoirs, the evaluation of the dual permeability behavior is the key to assess reservoir heterogeneity. This heterogeneity is expressed by highly variable and non-stationary reservoir properties. The 3D organization of these reservoir properties depends on the parameters, which dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 6 publications
0
19
1
Order By: Relevance
“…The TMU is sealed by the Laffan shales. Vadose zone indicators such as microstalactitic or meniscus cements are not observed in this study but are reported by Botton-Dumay et al (2002) in other wells of the reservoir 3.…”
Section: Large Dissolution Cavitiescontrasting
confidence: 66%
See 3 more Smart Citations
“…The TMU is sealed by the Laffan shales. Vadose zone indicators such as microstalactitic or meniscus cements are not observed in this study but are reported by Botton-Dumay et al (2002) in other wells of the reservoir 3.…”
Section: Large Dissolution Cavitiescontrasting
confidence: 66%
“…6). As proposed by Massonnat and Pernarcic (2002) and Botton-Dumay et al (2002) we attribute these features to a thick meteoric aquifer. Meteoric diagenesis below the TMU is commonly observed through the Middle East and is assumed to have a major impact on macroporous and microporous reservoirs (Burchette and Britton, 1985;Alsharhan and Nairn, 1993;Burchette, 1993;Alsharhan, 1995).…”
Section: Factor Controlling Distribution Of the C And F Petrophysicalmentioning
confidence: 51%
See 2 more Smart Citations
“…It was reported in this study that a large permeability of 5.5 Darcy assigned to vuggy zones resulted in a simulation match with the oil production and water cut histories. The permeability assignment and modeling for a large permeability zone was also studied by Massonnat et al (2002) Waterflood through vuggy carbonates was also studied by deZabala and Kamath (1995). Their core samples were from the Beaverhill Lake formation, Canada with a correlation length of 1 cm.…”
Section: General Carbonate Core Sample Studiesmentioning
confidence: 99%